Reaching middle-income status in Ghana by 2015: Public expenditures and agricultural growth - Benin, Samuel; Mogues, Tewodaj; Cudjoe, Godsway; Randriamamonjy, Josee (International Food Policy Research Institute, 2008)
Using district-level data on public expenditures from 2000 to 2006, and household-level production data from the 2005/06 Ghana Living Standards Survey, this paper estimates the returns to different types of public investments across four agro-ecological zones of Ghana. We then assess the amount of public agricultural expenditures required to raise agricultural growth to 6.9 percent per year until 2015, as this is the target growth needed for Ghana to achieve its goal of middle-income status. The results reveal that provision of various public goods and services has substantial impact on agricultural productivity. A one percent increase in public spending on agriculture is associated with a 0.15 percent increase in agricultural labor productivity, with a benefit-cost ratio of 16.8. Spending on feeder roads ranks second (with a benefit-cost ratio of 8.8), followed by health (1.3). Formal education was negatively associated with agricultural productivity. The estimated marginal effects and returns differ across the four agro-ecological zones. For Ghana to achieve middle income status by 2015, agricultural public spending should grow at an estimated rate of 19.6 percent per year, or by a total amount of GH¢264 million (or US$478 million) per year in 2000 prices over the 2005–2015 period. These requirements are lower if the government is able to achieve a higher efficiency in its public spending than the estimated elasticity of 0.15; this could potentially be achieved by reforming public institutions to improve the provision of agriculture-related public goods and services.